Supercritical Fluid Extraction and Chromatographic Analysis of Polynuclear Aromatic Hydrocarbons in Iligan City and Cagayan de Oro City Street Dusts: A Method Development and Application Study - Leopoldo, Girlie; Capangpangan, Mario (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
The development and application of optimized analytical procedures for the determination of selected polynuclear aromatic hydrocarbons (PAHs) namely naphthalene, phenanthrene, fluoranthene, pyrene, and benzo[a]pyrene in street dusts is described. Samples were extracted by supercritical fluid extraction (SFE), followed by concentration of the extract using Kuderna-Danish concentrator.Cleanup was done by passing the extract through silica gel column and eluting with 1:1 hexane/dichloromethane solvent mixture. Analysis was performed by HPLC with fluorescence detection. The developed SFE method achieved an overall accuracy of 99.86% with an overall precision of 9.48% RSD. The developed SFE-HPLC method was used to analyze street dust samples collected from Iligan City and Cagayan de Oro City representing concrete/heavily-trafficked, asphalt/heavily-trafficked, and asphalt/lightly-trafficked streets. PAHs concentration ranged from 0.005 to 12.04 microgram per gram (Og/g) with phenanthrene and fluoranthene concentrations found to be above the maximum permissible level for the protection of human health. Compared to asphalt, traffic has greater contribution to phenanthrene, fluoranthene, and pyrene concentrations.